Inhabitants of the Screen: Celebrity and the Production of Religious Authority in Bahian Candomblé - Port, Mattijs van de (Journal for the academic study of religion, 2011)
In Bahia, Brazil, the public articulation of religious authority comes to depend more and more on celebrity discourses. This article takes the Afro-Brazilian spirit possession cult Candomblé as an example to show how in media-saturated societies religious and media imaginaries become inextricably entangled. In their struggle to be publicly recognized as a proper ‘religion’, Candomblé priests ?nd themselves overcoming their media-shyness. Televisual fame is a value understood by the public at large, and its acquisition adds weight to the status and prestige of Candomblé priests in ways that religious criteria for priestly authority cannot accomplish.